Clinical and Genetic Factors Impact Time to Surgical Recurrence After Ileocolectomy for Crohn's Disease. Issue 2 (25th August 2021) - Kline, Bryan P.; Weaver, Taelor; Brinton, David L.; Harris, Leonard; Yochum, Gregory S.; Berg, Arthur S.; Koltun, Walter A.
Abstract : Objective: The aim of this study was to evaluate factors associated with time to surgical recurrence after Crohn's ileocolectomy. Summary Background Data: The most common surgery performed for Crohn's disease is ileocolectomy. Identifying patients at high risk for surgical recurrence may assist with medical and surgical decision-making. Methods: Data were obtained from 409 patients with Crohn's disease (CD) who had undergone ≥1 ileocolectomies at Penn State Hershey Medical Center. Six single-nucleotide polymorphisms (SNPs) associated with CD were evaluated in these patients: rs2076756, rs2066844, and rs2066845 in NOD2, rs4958847 and rs13361189 in IRGM, and rs2241880 in ATG16L1 . Genotype and clinical factors were analyzed to determine associations with time to recurrent ileocolectomy. A subgroup analysis was performed on 241 patients naïve to biologics before initial ileocolectomy to assess the effect of biologic therapy on time to recurrent surgery. Results: There were 286 patients who underwent a single ileocolectomy, whereas 123 required multiple ileocolectomies. Ileocolonic involvement [hazard ratio (HR) 1.90, 95% confidence interval (CI) 1.21–3.00, P = 0.006] and rs2066844 in NOD2 (HR 1.8, 95% CI 1.17–2.77, P = 0.007) were associated with decreased time to surgical recurrence by multivariate analysis. In patients naïve to preoperative biologics, the initiation of postoperative biologics was associated with a 40% decreased incidence of surgical recurrence (HR 0.60, CI 0.39–0.93, P = 0.02) over time. Conclusions: Ileocolonic distribution of disease and the rs2066844 SNP in NOD2 are associated with shorter time to recurrent ileocolectomy. The initiation of postoperative biologics in naïve patients was associated with a reduced incidence of recurrence over time.